Intrinsic Motivation of Mothers in Following the Al-Qur'an Recitation at Imaduddin Mosque Kampung Lapai Padang City - Tasia Apriani; Vevi Sunarti (Universitas Negeri Padang, 2020)
This research was motivated by the high participation of mothers in following the Al-Qur'an recitation at Imaduddin Mosque Kampung Lapai Padang City. This was evidenced by the learning participation of mothers who are seen from the desires, hopes, and satisfaction that are categorized high. The researcher suspect that the cause of the high participation of mothers is because it has to relate to the intrinsic motivation that exists in self mothers. This study aims to look at the picture of the intrinsic motivation of mothers in following the Al-Qur'an recitation at Imaduddin Mosque Kampung Lapai Padang City. This type of research is quantitative descriptive research. The population in this study were learning citizens who followed the Al-Qur'an recitation as many 19 people. Samples were taken as much as 75% of the total population of 14 people and used simple random sampling techniques. Data collection techniques using a questionnaire, while the data collection tools list the statements. Data analysis techniques use the percentage formula. The results showed that the: (a) Intrinsic motivation of mothers seen from the desire to follow the Al-Qur'an recitation at Imaduddin Mosque Kampung Lapai Padang City that are categorized high, (b) Intrinsic motivation of mothers seen from the hope to following the Al-Qur'an recitation at Imaduddin Mosque Kampung Lapai Padang City that are categorized high, and (c) Intrinsic motivation of mothers seen from the satisfaction to following the Al-Qur'an recitation at Imaduddin Mosque Kampung Lapai Padang City that are categorized high. This is evidenced by the majority of mothers giving statements very agree. Based on the results of the study it is recommended, for: (a) mosque administrator at Imaduddin Mosque Kampung Lapai Padang City in order to continue to improve each process of learning activities that have been carried out in the future in order to continue to develop and produce a quality learning that is useful and can maintain learning activities recitation Al-Qur’an especially older women so that they can benefit themselves and the wider community, and (c) the next researcher can be a guideline for researching about other variables of intrinsic motivation.Keywords: Intrinsic Motivation, Al-Qur’an Recitation